Assessment of Sustainable Use of Coastal Resources of Regional Waters Conservation Area Biak Numfor Regency, Papua Province, Indonesia - Sutaman Sutaman; Yusli Wardiatno; Mennofatria Boer; Fredinan Yulianda (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2017)
Efforts to exploit fish resources optimally, continuous and sustainable is an urgent demand for the greatest prosperity of the people, especially to improve the welfare of fishermen and fish farmers. The level of sustainable use of coastal resources in water conservation is very important, so that the utilization does not exceed the carrying capacity of the environment. The purpose of this study was to determine the level of sustainable use of coastal resources Biak Numfor, associated with the utilization of fisheries, aquaculture and tourism. The study was conducted in June to December 2015 and October to November 2016. The primary data obtained by interview and direct discussion through Focus Group Disscution (FGD) with fishermen community, tourist and tourist entrepreneurs as well as related officials in the Office of Fisheries and Marine Affairs, and Tourism Office of Biak Numfor Regency. Methods of data analysis approach sustainability analysis conducted by the method of MDS (Multi-Dimensional Scaling) with the help of software Rapfish. Based on the survey results revealed that the value of fisheries ordinated to achieve 57.66%, 44.80% aquaculture, and tourism 46.25%. With these achievements ordinated value, it can be concluded that the use of sustainable capture fisheries are still classified by the lever sustainability attributes include; the type of fishing gear, vessel types used and the catch per unit effort (CPUE). Meanwhile the relatively less sustainable aquaculture with the sustainability lever attributes include; cultivation technology, the number of business units with different types and species of fish. For tourism utilization is still considered less sustainable with levers sustainability attributes include the number of tourists, the type and number of amenities and facilities and infrastructure Keywords: Sustainability, utilization, waters conservation area (KKPD), MDS-Rapfish